A correction method of screw rotor profile error based on parameter adjustment for grinding wheel dresser. (September 2018) - Tao, Lijia; Xing, Yu; Yuan, Mingxin; Chen, Sijie
Accuracy of grinding wheel profile that is generated by form grinding theory and formed by grinding wheel dresser is a crucial factor affecting profile accuracy of screw rotors. A correction method for screw rotor profile error based on parameter adjustment for grinding wheel dresser such as diameter and distance of diamond rollers is proposed. Influence of diameter and distance of diamond rollers on grinding wheel profile and screw rotor profile based on theory of segmented dressing method is analyzed, and the adjustment method for parameters of grinding wheel dresser is presented. The results of the analysis provide a theoretical basis for error correction in screw rotor grinding. Grinding experiments for female rotor were performed due to the character that the female rotor has smooth bottom profile where the change of profile error is easy to observe. The experimental results show that the height difference between the long and short sides of rotor profile at the bottom of the rotor is significantly reduced from 0.22 mm to 0.034 mm by adjusting diameter of diamond rollers, and the distance between the long and short sides of the actual rotor profile is almost consistent with the theoretical one by measuring the distance again and adjusting its value in the computer numerical control system. These results verify the correctness of the correction method.